The Role of SEO Content Writer in Increasing The Organic Traffic of Akurat.co Website - Syafitri, Dinda Nur; Priatna, Wahyu Budi (Indonesian Scientific Publication, 2025)
This study examines the role of SEO Content Writers in increasing the organic traffic of the Akurat.co website. The rapid growth of digital media has reshaped how audiences access information, making Search Engine Optimization (SEO) an essential strategy for enhancing visibility and engagement in online journalism. Specifically, this study explores how SEO Content Writers contribute to improving organic traffic in a digital newsroom context an area that remains underexplored compared to general marketing focused SEO studies. Using a qualitative approach, data were collected through in depth interviews with three informants: a Senior Managing Editor of SEO as the key informant, supported by an SEO Content Writer and the Entertainment Editor of Akurat.co. Furthermore, literature studies were utilized to enrich the analysis and support data interpretation. The findings highlight that SEO Content Writers play a strategic role in keyword selection, content structuring, trend based topic analysis, and the production of evergreen articles that sustain long term visibility. Based on internal insights from the editorial team, approximately 80% of Akurat.co’s high traffic articles are driven by SEO based content, indicating a dominant contribution to organic readership (based on company estimation, not independent analytics tracking). In conclusion, SEO oriented content writing extends beyond technical optimization, serving as a core editorial strategy to maintain competitiveness in digital journalism.